2020
DOI: 10.1111/cen.14306
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of a conservative approach in cervical lymph node metastases of thyroid cancer

Abstract: Context Lymph node metastases (LNM) can be present in 35% of patients with differentiated thyroid cancer (DTC), and the management of persistent/recurrent nodal disease has been controversial. Watchful waiting may be a reasonable approach in selected patients, but uncertainty about clinical outcomes remains a concern. Objective To investigate the outcomes of patients with DTC with recurrent/persistent confirmed LNM under surveillance. Methods Patients with LNM from DTC were selected from databases of needle wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…However, all patients who met the inclusion criteria were followed prospectively and treated following the same protocol and according to current ATA and local guidelines ( 3 , 21 ). Another limitation may be the relatively short length of follow-up (median of 4.3 years), although it is longer than previous published series in the field ( 7 - 9 , 11 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, all patients who met the inclusion criteria were followed prospectively and treated following the same protocol and according to current ATA and local guidelines ( 3 , 21 ). Another limitation may be the relatively short length of follow-up (median of 4.3 years), although it is longer than previous published series in the field ( 7 - 9 , 11 ).…”
Section: Discussionmentioning
confidence: 93%
“…All of these series included patients with a profile similar to ours, although there are some interesting differences. Considering that one of the concerns in this setting is the rapid growth and invasion into adjacent structures, some series excluded patients with aggressive histologic subtypes ( 7 , 8 ). In our series, 4 (12.6%) patients had tall cell or hobnail subtype PTC and were not excluded because 3 (75%) initially had intermediate risk of recurrence solely because of the subtype, and the other presented with a single sub-centimeter lung metastasis that was effectively treated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…revealed an LNM incidence of <5% based on 5-10 years of PTMC data, and all new metastases appeared in the lateral compartment instead of the central compartment ( 5 , 30 , 31 ). Compared to PTC, which has an incidence range of 30-90%, PTMC is less prone to LN involvement, which suggests that PTC of a small size exhibits less nodal invasion ( 16 , 32 ). We found that even for PTMC, compared to size > 5 but ≤ 10 mm, size ≤ 5 mm significantly increased the possibility of pCLN-, which obtained the highest score on the nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic drainage of the lower thyroid is primarily collected by the lymphatic vessels accompanying the inferior thyroid artery and flowing into the lateral lymph nodes through the CLNs (especially the paratracheal lymph nodes) and ultimately into the venous system. Lymphatic drainage from the isthmus of the thyroid primarily descends to the mediastinal lymph nodes (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment of PTC is thyroidectomy followed by selective radioiodine ablation and/or thyroxine therapy (9,10). However, recent evidence suggests that use of more conservative approaches as well as radioiodine ablation, especially in low risk PTC, are equally effective (11)(12)(13)(14). Hence, these treatment approaches, when used in risk defined patients, can reduce the disease recurrence and improve patients' outcome.…”
Section: Introductionmentioning
confidence: 99%